IN VITRO CALLUS INDUCTION OF ‘SHIRAZ’ GRAPE (Vitis vinifera L.) USING DIFFERENT MEDIUM AND GROWTH REGULATOR COMBINATION - Ni Nyoman Nila Arieswari; Ida Ayu Astarini; Ni Putu Adriani Astiti; Jeremy Pramana (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2018)
One of grape cultivars widely used as raw material for wine production is ‘Shiraz’ cultivar. Propagation of this cultivar is necessary for the provision of grape as a wine making material in Bali. In vitro culture is an alternative propagation technique than can be employed to produce planting materials in a shorter time. This research aims to determine the most suitable medium and growth regulator combination in inducing grape cv. ‘Shiraz’ callus in vitro. The study was conducted from November 2017 until February 2018 at Plant Tissue Culture Laboratory, Biology Study Program, Udayana University. The explants used were young stem of grape cv. ‘Shiraz’ and the experiment was conducted using factorial design with two factors. The first factor was basal medium used (MS and WPM) and the second factor was IBA concentration (0; 0.5 and 1 mgL-1) and BAP (0, 1 and 2 mgL-1). The results showed that the highest percentage of callus induction (60%) was obtained on WPM medium without growth regulator combination (control). However, the fastest time of callus appear was on MS medium + 2 mgL-1 BAP without IBA, which was 17 days after planting. The texture and color of callus resulted on this research were friable with white, greenish white, greenish yellow and green in color.